2019
DOI: 10.1021/acs.joc.9b01924
|View full text |Cite
|
Sign up to set email alerts
|

Rh(II)-Catalyzed Denitrogenative Transannulation of N-Sulfonyl-1,2,3-triazolyl Cyclohexadienones for the Synthesis of Benzofurans and Cyclopropa[cd]indole-carbaldehydes

Abstract: A rhodium-catalyzed intramolecular denitrogenative transannulation of N-sulfonyl-1,2,3-triazole-tethered cyclohexadienones has been achieved for the synthesis of benzofurans and cyclopropa­[cd]­indole-carbaldehydes in an operationally simple procedure. Remarkably, the reaction pathway is fully dependent on the linker heteroatom (O or N) present between the cyclohexadienone unit and triazole moiety. In the case of O-linked triazoles, a cascade sequence consisting of intramolecular cyclopropanation and rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…On the other hand, recent years have seen the resurgence of vinyl cation intermediates in synthetic chemistry, especially due to their facile generation under metal-free acidic conditions . With our interest in the diverse reactivity of alkynyl cyclohexadienones, , we envisioned that, upon activation by an acid, they could generate a bicyclic vinyl cation intermediate B by interrupting the otherwise ensuing, dienone–phenol rearrangement from A . Therefore, tailoring upon this, herein, we report a metal-free Brønsted acid-catalyzed water mediated rearrangement of alkyne tethered cyclohexadienones to access meta -alkenylated phenols …”
mentioning
confidence: 99%
“…On the other hand, recent years have seen the resurgence of vinyl cation intermediates in synthetic chemistry, especially due to their facile generation under metal-free acidic conditions . With our interest in the diverse reactivity of alkynyl cyclohexadienones, , we envisioned that, upon activation by an acid, they could generate a bicyclic vinyl cation intermediate B by interrupting the otherwise ensuing, dienone–phenol rearrangement from A . Therefore, tailoring upon this, herein, we report a metal-free Brønsted acid-catalyzed water mediated rearrangement of alkyne tethered cyclohexadienones to access meta -alkenylated phenols …”
mentioning
confidence: 99%
“…It was also shown that the use of O‐linked triazoles in this transformation led to benzofuran derivatives 51 through an oxy‐Cope rearrangement. In the same year, Volla and co‐workers realized the same reactions under Rh 2 (oct) 4 catalysis in CHCl 3 as solvent at 90 °C …”
Section: Denitrogenative Cyclization Of Triazolesmentioning
confidence: 98%
“…The groups of Volla and Shi individually reported the synthesis of benzofurans 32.2 and cyclopropa­[ cd ]­indoles 32.3 through intramolecular cyclopropanation of alkenes from triazole 32.1 containing a tethered cyclohexadienone group in which an O or N atom is present in the linker (Scheme ). Mechanistically, the Rh-bound iminocarbenoid intermediate 32.4 is initially formed from triazole 32.1 and the Rh catalyst.…”
Section: Denitrogenative Transformations Of Triazolesmentioning
confidence: 99%